Diagnosis of Uncomplicated and Complicated Appendicitis in Adults - Bom, W. J. (Scand J Surg, 2021)
BACKGROUND: Diagnostic work-up of acute appendicitis remains challenging. While some guidelines advise to use a risk stratification based on clinical parameters, others use standard imaging in all patients. As non-operative management of uncomplicated appendicitis has been identified as feasible and safe, differentiation between uncomplicated and complicated appendicitis is of paramount importance. We reviewed the literature to describe the optimal strategy for diagnosis of acute appendicitis. METHODS: A narrative review about the diagnosis of acute appendicitis in adult patients was conducted. Both diagnostic strategies and goals were analyzed. RESULTS: For diagnosing acute appendicitis, both ruling in and ruling out the disease are important. Clinical and laboratory findings individually do not suffice, but when combined in a diagnostic score, a better risk prediction can be made for having acute appendicitis. However, for accurate diagnosis imaging seems obligatory in patients suspected for acute appendicitis. Scoring systems combining clinical and imaging features may differentiate between uncomplicated and complicated appendicitis and may enable ruling out complicated appendicitis. Within conservatively treated patients with uncomplicated appendicitis, predictive factors for non-responsiveness to antibiotics and recurrence of appendicitis need to be defined in order to optimize treatment outcomes. CONCLUSION: Standard imaging increases the diagnostic power for both ruling in and ruling out acute appendicitis. Incorporating imaging features in clinical scoring models may provide better differentiation between uncomplicated and complicated appendicitis. Optimizing patient selection for antibiotic treatment of appendicitis may minimize recurrence rates, resulting in better treatment outcomes.